Clinical significance of polyunsaturated fatty acids in the prevention of cardiovascular diseases - Kotlyarov, Stanislav; Kotlyarova, Anna (Frontiers in Nutrition, 2022)
Cardiovascular diseases are one of the most important problems of modern medicine. They are associated with a large number of health care visits, hospitalizations and mortality. Prevention of atherosclerosis is one of the most effective strategies and should start as early as possible. Correction of lipid metabolism disorders is associated with definite clinical successes, both in primary prevention and in the prevention of complications of many cardiovascular diseases. A growing body of evidence suggests a multifaceted role for polyunsaturated fatty acids. They demonstrate a variety of functions in inflammation, both participating directly in a number of cellular processes and acting as a precursor for subsequent biosynthesis of lipid mediators. Extensive clinical data also support the importance of polyunsaturated fatty acids, but all questions have not been answered to date, indicating the need for further research.